Xtend® packaging and Aloe vera coating benefit shelf life and safety maintenance of fresh shiitake mushrooms - Gonçalves da Silva, Vitor; Bassani Hellmeister Dantas, Tiago; Moitinho, Daisy; Colares Souza Usberti, Franciane (Revista Ciência Agronômica, 2022)
The consumer market has expanded its search for foods combining sensory, nutritional, and bioactive attributes, which puts edible mushrooms in evidence. However, their production chain still has deficiencies to prevent mechanical damage, microbiological contamination, perishability, and weight loss during storage, factors closely associated with unsuitable packaging of the product. This study aimed to evaluate whether different packaging configurations, associated with the application of edible Aloe vera gel coating, preserve shelf life and safety of fresh shiitake mushrooms throughout their storage, especially as a replacement for standard packaging. The experiment was conducted with fresh shiitake mushrooms, with a completely randomized design in a 3 x 2 x 4 factorial scheme, with three packaging configurations (EPS PVC, EPS PVC perforated, Xtend®), 2 coating conditions (with and without Aloe vera gel coating), four storage times (0, 3, 7 and 10 days), with four repetitions. For each storage time, weight loss, visual aspect, CO2 concentration in the package, and microbiological evaluations were assessed. In conclusion, use of Aloe vera coating on shiitake mushrooms preserves their quality attributes and promotes food safety through antimicrobial action, extending their shelf life. Xtend® packaging is potentially suitable to replace EPS PVC packaging in the sale of fresh mushrooms, reducing weight loss and preserving food quality and safety.